462. Prevalence and Outcome of Asymptomatic Procedural Patients with COVID-19 Infection. (31st December 2020) - Maki, Gina; Abdollah, Firas; Dabaja, Ali; Suleyman, Geehan
Abstract: Background: Guidelines recommend testing for SARS-COV-2 in asymptomatic individuals who are undergoing time-sensitive major surgery or aerosol generating procedures (AGPs) to guide infection prevention practices, including PPE use, and minimize risk of potential poor outcomes associated with COVID-19 infection by delaying the procedure in positive patients. However, evidence to support these recommendations are limited. We describe the outcome of asymptomatic patients with SARS-COV-2 undergoing surgery or AGPs. Methods: We implemented a system-wide policy to test all patients requiring intubation or other AGPs at Henry Ford Health System (HFHS), a 5-hospital system in southeast Michigan. This was a retrospective review of asymptomatic surgical patients with COVID-19 infection between 5/1/2020–5/31/2020. All patients with positive polymerase chain reaction (PCR) of upper respiratory tract were included. Demographics, comorbidities, procedural/surgical categories, symptoms and outcomes were evaluated. Results: 4381 COVID-19 PCR tests were performed pre-procedurally during the study period, of which 18 (0.4%) were positive. Summary of characteristics is presented in Table 1. Mean age was 49.7 years, and the majority were female (61%) and black (67%). Six (33%) of 18 surgeries were performed despite positive COVID-19 PCR as shown in Table 2. Of those who had the procedure performed, none developed symptoms within 14 days. Two (11%) patients developed symptoms within 14 days of positive PCR after their procedures were canceled. None of those who had their procedure delayed developed any symptoms. Of the total patients, none required hospitalization or died. Table 1. Characteristics of asymptomatic patients with COVID-19 infection Table 2. Outcome of procedure in asymptomatic patients with COVID-19 Conclusion: The prevalence of COVID-19 infection was very low in our asymptomatic patient population. Decisions around SARS-CoV-2 testing in asymptomatic patients undergoing procedures should be based on exposure history and prevalence of disease in the community to avoid unnecessary testing and diversion of resources away from symptomatic patients. Disclosures: All Authors : No reported disclosures